Detection and Characterization of Resistant Gene in Tomato Seeds of PHS165, Hyveg, and Cynus Hybrid Varieties - Vemuri, Praveen Kumar (Asian Journal of Pharmaceutics (AJP), 2023)
Background: The demand for tomato is increasing day by day mostly because of the increased per capita fresh fruit consumption. Nonetheless, as a perishable fruit crop, it has relatively short life after ripening thus experiences remarkable post-harvest losses. Aims: Our approach in this study is to evaluate the consistency and purity of seeds that are developed to control pest resistance. Methods: Touchdown polymerase chain reaction (TD-PCR) and Fourier transform infrared studies are used to test seed genetic purity of three commercial hybrid tomato seeds PHS165, HYVEG, and CYGNUS varieties. TD-PCR is a sensitive and specific method and can be used to detect even low levels of genetic impurities. Results: Amplicon of 550bp toward Cry2abresistant gene was found in CYGNUS and HYVEG varieties. Results might suggest that these commercial hybrid tomato seeds may contain genetic material from Bacillus thuringiensis that confers resistance to Cry2ab toxin. Conclusion: In the present study, the purity of tomato hybrid was assessed by both PCR-based and analytical methods-based screening of commercial tomato hybrids. Further testing and analysis may be necessary to confirm the presence and origin of the Cry2ab-resistant gene in these commercial hybrid tomato seeds and to determine the potential impact on crop yield and pest management strategies.